International liability for transboundary damage arising from stratospheric aerosol injections. (2nd January 2015) - Saxler, Barbara; Siegfried, Jule; Proelss, Alexander
Abstract : The large-scale implementation of stratospheric aerosol injection (SAI) may potentially lead to disastrous transboundary damage. Before implementation of this technique is initiated, it is crucial to address the issue of compensation for potential victims of such damage. However, international law does so far not provide for a specific liability regime for SAI. This study assesses if and to what extent existing international rules on liability could be applicable to SAI damage. Apart from the assessment of the rules on State responsibility, the question whether States can generally be held internationally liable for damage arising from lawful activities is addressed. In addition, liability regimes concerning ultra-hazardous activities that are comparable to SAI are analysed, taking into account their potential relevance for the design of a future SAI liability regime. The issue of uncertainty is particularly challenging in the context of SAI, as usually evidence concerning the causality between implementation and potential damage would have to be produced. The study concludes that existing international liability rules are not capable of providing equitable and effective compensation for SAI damage. Still, valuable approaches can be found in these regimes in order to identify the main elements which a future SAI liability regime would have to address in order to ensure such compensation.